2006
DOI: 10.1051/0004-6361:20054378
|View full text |Cite
|
Sign up to set email alerts
|

On the fine structure of sunspot penumbrae

Abstract: In this paper we study the fine structure of the penumbra as inferred from the uncombed model (flux tube embedded in a magnetic surrounding) when applied to penumbral spectropolarimetric data from the neutral iron lines at 6300 Å. The inversion infers very similar radial dependences in the physical quantities (LOS velocity, magnetic field strength etc.) as those obtained from the inversion of the Fe I 1.56 µm lines. In addition, the large Stokes V area asymmetry exhibited by the visible lines helps to constrai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
55
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 34 publications
14
55
0
Order By: Relevance
“…Assuming more than one magnetic component or gradients along the line of sight, high-resolution polarimetric studies present evidence for magnetic flux that returns to the surface in the outer penumbra (e.g. Westendorp Plaza et al, 2001;Bellot Rubio, Balthasar, and Collados, 2004;Borrero et al, 2004Borrero et al, , 2006Langhans et al, 2005;Ichimoto et al, 2007Ichimoto et al, , 2009Beck, 2008;Jurčák and Bellot Rubio, 2008), i.e. there is evidence that a fraction of the sunspot magnetic field does not extend into the chromosphere, but submerges beneath the photosphere in the outer penumbra.…”
Section: Field Strength and Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming more than one magnetic component or gradients along the line of sight, high-resolution polarimetric studies present evidence for magnetic flux that returns to the surface in the outer penumbra (e.g. Westendorp Plaza et al, 2001;Bellot Rubio, Balthasar, and Collados, 2004;Borrero et al, 2004Borrero et al, , 2006Langhans et al, 2005;Ichimoto et al, 2007Ichimoto et al, , 2009Beck, 2008;Jurčák and Bellot Rubio, 2008), i.e. there is evidence that a fraction of the sunspot magnetic field does not extend into the chromosphere, but submerges beneath the photosphere in the outer penumbra.…”
Section: Field Strength and Orientationmentioning
confidence: 99%
“…• Bellot Rubio (2003) and Borrero et al (2004Borrero et al ( , 2005Borrero et al ( , 2006: Inverted the polarization profiles from the penumbra and considered the uncombed penumbral model with two magnetic components, where the component with a more horizontal and weaker field harbors the Evershed flow.…”
Section: Penumbral Models and Spatially Resolved Modelsmentioning
confidence: 99%
“…These and other recent high-resolution Stokes data do not provide evidence for flow channels and flux tubes elevated above the photosphere, as discussed in some papers, e.g., Solanki & Montavon (1993); Rimmele (1995); Borrero et al (2006). Based on observations of penumbra magnetic fields, interpretations in terms of convective gaps or flux tubes partly buried below the τ = 1 surface thus are inherently ambiguous.…”
Section: Connections To Flux Tube Modelsmentioning
confidence: 67%
“…These calculations demonstrate consistency between the calculated azimuthal variation of NCP and measurements made at low spatial resolution in visible and near infrared spectral lines. Two-component inversions interpreted within the context of embedded flux tube models and applied to low spatial resolution (0.6-1 arcsec) Stokes data by Borrero et al (2004Borrero et al ( , 2005Borrero et al ( , 2006 similarly were shown to be largely consistent with the assumed inversion (flux tube) model.…”
Section: Embedded Flux Tubesmentioning
confidence: 69%
See 1 more Smart Citation